Fruits and vegetables intake among Costa Rican urban population: results from the Latin American Study of Nutrition and Health: ELANS-Costa Rica - Gómez Salas, Georgina; Quesada, Dayana; Chinnock, Anne (Población y Salud en Mesoamérica, 2020)
Introduction: Consumption of fruit and vegetables has been widely associated with different health benefits such as protection against non-transmissible chronic diseases, cancer and mental disorders. Due to these benefits, the World Health Organization (WHO) recommends daily consumption of 400 grams of fruit and vegetables. This study is aimed at characterize fruit and vegetable consumption according to socioeconomic variables, among the Costa Rican population and the degree to which this meets the WHO recommended intake. Methods: Data were obtained from the Latin American Nutrition and Health Study (ELANS)-Costa Rica. 798 subjects aged 15-65 years, living in urban areas were interviewed and their food consumption assessed by two 24-hour Recalls. Fruit and vegetable consumption were analyzed by gender, age group and socioeconomic status. Results: Average daily consumption of fruit and vegetables was 220g/p/d and increased with age (p=0.035 between with 15-19 and 50-65 years old) and socioeconomic status (p=0.004 between low and middle). No association was found with gender or education level (p>0.05). Only 12.0 % of the urban Costa Rican population met the WHO recommendation. Conclusions: The results provide evidence for the need for programs and interventions adapted to the characteristics and preferences of the Costa Rican population, to promote an increase of the consumption of fruits and vegetables. Similar studies are needed in the rural areas of Costa Rica as food habits and factors associated with them may differ